(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
With the advancement incellular phone technologies and invention of better and smaller processors, batteryand electronic displays. While phones have not been plagued with spywares andviruses like computers but with the myriad connectivity options as well asadvent of high speed 3G and 4G networks, the threat cannot be ignored. Whileenabling interoperation with the internet brings tremendous opportunities inservice creation and information access, the security threat of the Internetalso dauntingly extends its reach. Users keep lots of important contacts andother private information. Native security like password protection had alwaysexisted but what about the naive users who did not set a password forefficiency and ease. Even if phone is password protected a hacker could easilyswitch memory cards and gain access to confidential data. Not only data butwith GPS chips embedded in such phones, the whereabouts of the person are alsoexposed. Today’s Smartphone operating systems frequently fail to provide userswith adequate control over and visibility into how third-party applications usetheir private data .Malware on device can create number of risks which createsproblem while connectivity because of security issues. Many honest end usersare being successfully hacked on a regular basis. With this research paper Iwish to delve into the different security issues that are currently plaguingthe Smart Phones, the risk they are posing, as well as the manufacturers areusing to handle them.